SOCIAL MEDIA IMPACT OF KEDIRI ELECTION COMMISSION IN INCREASING PARTICIPATION ELECTION IN 2024 - An-Nasser, Ababil; Retpitasari, Ellyda; Inayah, Aizzatul; A.L, Dea Vanessa; Ihsani, A. Fikri Amiruddin (Universitas Islam Negeri Mataram, 2024)
Social media has an important role in socializing the 2024 elections. The 2024 elections cannot run well if there are no stages carried out beforehand. Researchers used a qualitative descriptive approach, through a process of direct observation and interviews at the Kediri District General Election Commission. The impact of communication through social media in increasing participation in the 2024 General Election is known that the number of voter participation has increased significantly to 83.75 percent in Kediri District. With the number of beginner voter participation consisting of generation Z and Millennial Generation almost 50%. The details of Generation Z reached 212,585 people, and the Millennial Generation reached 372,022 people.